2019
DOI: 10.18502/kss.v3i21.4988
|View full text |Cite
|
Sign up to set email alerts
|

Housing Morphology and Connectivity Quality in Periphery of Bandung City: Space Syntax Analysis

Abstract: The complexity that occurs in the city is determined by its diversity and intensity of inhabitant activity. The connectivity system becomes an essential factor to accommodate these lively activities, especially connectivity of the housing area to the working area and public facilities. Periphery area of some metropolitan city including Bandung City has been growing fast, which is influenced by the intense need for housing accommodation, as well as accommodation of educational and industrial sectors. The East P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the ASA model, NACH and NAIN are also adopted in accordance with methods put forward by Hiller et al [26]. The values of NAIN and NACH can be calculated by Formulas ( 2) and (3).…”
Section: Methods Of Quantitative Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ASA model, NACH and NAIN are also adopted in accordance with methods put forward by Hiller et al [26]. The values of NAIN and NACH can be calculated by Formulas ( 2) and (3).…”
Section: Methods Of Quantitative Estimationmentioning
confidence: 99%
“…The 'Intelligibility' index is an indicator of the correlation between the local and the whole in a spatial system. Relevant empirical studies [26] have shown that the intelligibility of space is higher, and visitors will not easily get lost in space, and vice versa. The 'Intelligibility' index can be calculated by the Formula (4).…”
Section: Methods Of Quantitative Estimationmentioning
confidence: 99%